2019
DOI: 10.1016/j.jclepro.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Consolidating the current knowledge on urban agriculture in productive urban food systems: Learnings, gaps and outlook

Abstract: Urban agriculture is of increasing interest for tackling a range of environmental and social issues of the current food systems. However, many questions remain unanswered regarding upscaling, the balancing of its multipurpose nature, and how it should be embedded into the broader urban system. This review looks at a breadth of novel insights that are indicative for sensible future development, including new possibilities for nutrient circularity, opportunities for increased sustainability and open questions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 106 publications
(123 reference statements)
3
69
0
2
Order By: Relevance
“…The results of this study seem to be consistent with a recent review which found critical issues of sustainability for UA, especially for cereals and calories provisioning potentials [47]. This view is supported by Martellozzo et al [48] who carried out a global analysis of the spatial constraint to meet the vegetable consumption on urban areas, asserting that UA cannot satisfy food self-provisioning, especially for densely populated cities.…”
Section: Practical Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study seem to be consistent with a recent review which found critical issues of sustainability for UA, especially for cereals and calories provisioning potentials [47]. This view is supported by Martellozzo et al [48] who carried out a global analysis of the spatial constraint to meet the vegetable consumption on urban areas, asserting that UA cannot satisfy food self-provisioning, especially for densely populated cities.…”
Section: Practical Implicationssupporting
confidence: 91%
“…Strong evidence of vertical farming potential was recently reported by Sanjuan-Delmás et al [56] in a feasibility study, reporting productivity of 19.6 kg/m 2 /year of tomato simultaneously reducing CO 2 emissions and using rainwater collected from buildings. Promoting conversion to vegetable production could open new pathways for innovative growing practices (e.g., aquaponics, hydroponics, rooftop greenhouses, micro-scale anaerobic digestion) [47], upgrading resource-use efficiency and circularity by integrating composting and organic waste flows, as well as biodiversity enhancement and habitat conservation [57].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Depending on the type of UA, the product and the agronomic practices, such reductions result in the decrease of the environmental impact in the LCA indicators related to carbon emissions and air pollution associated with the food product [15,25,62,63]. However, the logistics of UA can lead to less efficient distribution models (e.g., smaller truck capacity, consumer transportation to the farm or to the pick-up point), and the environmental benefits depend on the logistics model implemented in each specific case [64]. Highlighting the positive aspects of the vegetative structure, the inclusion of diverse native plants and the re-naturalization of urban areas for sustaining biodiversity and pollination ecosystem services, Lin et al [65] reviewed the literature regarding biodiversity and UA.…”
Section: Contrasting the Evidence Of The Most Frequent Sustainabilitymentioning
confidence: 99%
“…Several benefits of urban agriculture (UA) have been mentioned in the literature, including ecosystem services provisioning, social values, and health benefits (Clinton et al 2018;Weidner et al 2019). In this article, however, we focus on the contribution of UA to urban household food security (FS).…”
Section: Introductionmentioning
confidence: 99%